PENINGKATAN MOTORIK HALUS ANAK MELALUI KEGIATAN MEROBEK KERTAS PADA ANAK USIA 4-5 TAHUN TK NEGERI 2 SAMARINDA - Vivi Endang Adiningsih; Rizqi - Syafrina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2019)
Children cannot use their fine motoric skill well in paper-tearing activity. It seems that there are still many children who do not participate in the paper tearing activity, as exemplified by the teacher. This is proven when children do paper tearing activities. The aim of this research is to improve children's fine motor skills through paper tearing on children aged 4-5 years. The method used in this study is classroom action research (CAR) and a descriptive research which carried out in two cycles consisting of 3 meetings in each cycle. Research procedures that were carried out in this study were planning, implementation, observation and reflection. The subjects of this study were 19 children aged 4-5 years, consisted of 7 boys and 12 girls. The results showed that the children's fine motor skills improved compared to the pre-cycle phase. In cycle I, there was an increase from pre-cycle with an average value of 31.3% to 60.9% through the first, second and third meeting and succeeded in the second cycle through the first, second and third meeting with an average value of 87.4% in which this value has reached the target of success indicator that is 85%. Based on the results of the study, it can be concluded that paper tearing activity can improve children aged 4-5 years’ fine motoric skills and it is suggested to kindergarten teachers to make paper tearing activities as a media for improving children's fine motoric skills.